Projeto de controladores não lineares para voo autônomo de veículos aéreos de pás rotativas - Brandão, Alexandre Santos (2013)
This Ph.D. Thesis proposes nonlinear controllers to guide rotary-wing unmanned aerial vehicles (UAV) to accomplish tasks of positioning, trajectory tracking and path following in the 3D space. Two cases are addressed: the UAV is navigating alone or in cooperation with an unmanned ground vehicle (UGV). Initially the dynamic model of the rotorcraft is presented, obtained by using the Euler-Lagrange formulation and the Newton-Euler formulation as well. In addition, it is presented the representation of a UAV (helicopter or quadrotor) focusing on the underactuated characteristic of the model developed for the aircraft (the variables to be controlled are more than the control signals available). Considering the flight missions themselves, as a first step some restrictions of movement are applied to the aircraft, such that its movement become restricted to the Z axis and, in the sequel, to the XZ and Y Z planes, referenced to the inertial frame. For such cases, PVTOL (Planar Vertical Takeoff and Landing) controllers capable of guiding the aircraft in taking-off, hovering and landing are proposed. The stability of the control system implemented using such controllers, in Lyapunov’s sense, is demonstrated, and the controllers are validated through simulated and experimental results. In the sequel, the flight restrictions are relaxed, and the UAV becomes able to fly in the 3D space. At this point, a important contribution of this work is the proposal of a nonlinear controller based on partial feedback linearization, considering the high coupling between the active/actuated and passive/nonactuated parts of the underactuated system. Simulated and experimental results validate the proposed controller to be used in the classical classes of movement control in Robotics. Following, it is presented a proposal of a switching scheme associated to the PVTOL controllers previously proposed, so that it becomes possible to use simpler controllers to guide the aircraft in a 3D flight mission. Finally, this Thesis also presents a control scheme to guide the navigation of a UAV in coordination with a UGV (or a group of UGVs). The leader-follower control strategy is adopted, to allow the UAV to track the UGV, which is labeled the leader of the formation. Notice that the controllers adopted for guiding the UAV and the UGV work in a completely independent way, with the leader-follower approach being an upper layer responsible for coordinating the poses of the two vehicles. The stability of the control system using such controller is proven, using Lyapunov’s theory, and simulated and experimental results also shown validate the proposed control scheme.